Qadzaf Dalam Perspektif Hadits: Analisis Syarah Hadits Metode Ijmali - Gunawan, Heru (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2021)
Ijmali method is a method of explaining hadith with systematics arranged in the order contained in the book described briefly, and globally. At its core, ijmali is a method of explaining globally not long-winded. But, sometimes there is also a detailed discussion so that the meaning in the hadith can be conveyed well. Hadith that the author describes is a hadith that discusses the 7 great sins in the sight of Allah. Such sins include, associating others with Allah, magic, killing a soul forbidden by God except those who have the right to killed, eating usury, eating the property of orphans, fleeing the battlefield, and accused of adultery against a muslim woman who guarded her honor. The focus of the writers' group discussion is accusing women of faith adultery or qadzaf. in this hadeeth it is clear that accusations of adultery to women who believe in Allah and keeping his honor is a grave sin and forbidden. The punishment for this qadzf perpetrator is whiping 80 times.